Estrategias de campaña virtual en la segunda vuelta presidencial: Ecuador 2021 (Monográfico) - Chipuxi Llivi, Dayanna Mishell (2023)
The presidential runoff in Ecuador was developed through virtual environments mainly because of the COVID-19 pandemic between the finalist candidates Andrés Arauz and Guillermo Lasso. This research proposed the identification of political marketing characteristics and the level of engagement achieved by both candidates on platforms such as Facebook and TikTok. Through qualitative and quantitative techniques such as in-depth interviews, observation sheets and engagement measurement. In conclusion, it was determined that the winner achieved greater interaction on TikTok than on Facebook, which gave a closer and more spontaneous character to his campaign. The marketing strategies focused on disassociating the candidates from the traditional stereotype.